The crossover among the incas in the Collasuyu - Moyano Vasconcellos, Ricardo Fernando (2016)
We present archaeoastronomical and ethnohistorical evidence related to the ushnu and the spring equinox full Moon on Inca contexts, in central-northern Chile and northwestern Argentina (1470-1536 AD). From the perspective of the landscape archaeology and the astronomy in culture we analyze the lunar cycles of 18.03,18.61, and 19 years, including synodic and intercalary months. As hypothesis we assume the use of the Citua ceremony, in the lunar month of September, to determinate the solar year of 365 days and the 354 days lunar cycle, useful to predict eclipses (1 Metonic ? 12 lunar months = 1 Saros). The analysis of twelve Incan sites in the Collasuyu, between the 18.5° and 34° south latitude, show us the importance of architecture, rock art, the gnomon, and horizon landmarks, to determinate not only solstices and equinoxes, but also major and minorlunar standstills, and the crossover related to the full Moon. We conclude that the Incas were able to predict lunar eclipses, with political and ideological purposes, thanks the use of these astronomical cycles in ritual contexts. In other words, a mnemonic system that allowed coordinates the main ceremonial activities with lunar and solar cycles within the Inca ceque calendar.